2019
DOI: 10.3390/en12112226
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Interconnections between Supply or Demand Side and Oil Risks

Abstract: Due to the crucial implication of oil risks for economic growth and policy making, the aim of this paper is to explore the heterogeneous interconnections of supply or demand in oil risks over time horizons and different countries. Specifically, we first examine the correlation of supply or demand in oil return risks and show the relationships in different countries based on wavelet coherence. Furthermore, we explore the time-varying interconnections between supply- or demand-side and oil return risks, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…In this section, we will review the literature on the subject and laid the foundation for analyzing the determinants of INE crude oil volatility. From the perspective of economic relations between commodity supply and demand and the oil prices, previous literature have shown that demand, supply, and speculation are the driving forces of oil price volatility (Narayan and Narayan, 2007;Mu and Ye, 2011;Kilian and Murphy, 2014; Pan et al, 2017;Yi et al, 2018;Liao et al, 2019). However, as a commodity that is traded globally, the crude oil market faces a much more complicated economic environment and might be driven by other macroeconomic factors beyond its supply and demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section, we will review the literature on the subject and laid the foundation for analyzing the determinants of INE crude oil volatility. From the perspective of economic relations between commodity supply and demand and the oil prices, previous literature have shown that demand, supply, and speculation are the driving forces of oil price volatility (Narayan and Narayan, 2007;Mu and Ye, 2011;Kilian and Murphy, 2014; Pan et al, 2017;Yi et al, 2018;Liao et al, 2019). However, as a commodity that is traded globally, the crude oil market faces a much more complicated economic environment and might be driven by other macroeconomic factors beyond its supply and demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this impact is a conflicting issue among different stakeholders [3]. For one thing, the correlation between OPEC and oil price varies over a time horizon, because of the changing market share of non-OPEC oil production [4]. For another, the role of OPEC changes over time due to the market fundamentals.…”
Section: Introductionmentioning
confidence: 99%
“…In macro terms, a decreasing oil production capacity has an impact on the adequacy of energy services when needed in the Metropolitan Mamminasata area. The crude oil price chain is affected by different types of interconnections in different time windows [112].…”
Section: Energy Security and Use Of Renewable Energymentioning
confidence: 99%